Framing Kebangsaan Melalui Dakwah Kultural: Strategi Komunikasi Politik Kh. Abdullah Syafi’ie - Ihsan Abdul haq; Edison Bonar Tua Hutapea (Hadara : Journal of Da'wah and Islamic Civilization, 2026)
Strengthening national consciousness faces increasingly complex challenges due to globalization, identity politics, and information disruption in the digital age. These conditions call for a model of political communication capable of contextualizing national values through an approach that is closely attuned to the social realities of the community. This study aims to analyze national framing through cultural da’wah (preaching) implemented by K.H. Abdullah Syafi’ie as a political communication strategy in building national consciousness. The method used is qualitative research with a descriptive-interpretive approach through discourse analysis of K.H. Abdullah Syafi’ie’s sermons, da’wah practices, and thoughts within a socio-religious context. The results of the study indicate that K.H. Abdullah Syafi’ie frames national consciousness through Islamic values such as amanah, ukhuwah, unity, and the common good, which are communicated through a cultural da’wah approach using symbolic and cultural language that resonates with the community. This framing produces a national identity that is inclusive, religious, and adaptive to social dynamics. The novelty of this study lies in the integration of the framing perspective into the study of political communication and cultural da’wah to explain the formation of national consciousness at the grassroots level. The findings of this study suggest that cultural da'wah can serve as an effective instrument of political communication in strengthening social cohesion and national resilience amid the challenges of the digital age.